Switching costs in the Finnish retail deposit market - Tuomas Takalo (Bank of Finland, 2019)
I calibrate switching cost for the Finnish retail deposit market by using the approach developed by Oz Shy (2002). It turns out that switching costs faced by deposit customers of the main banks are high, ranging from 200 euros to nearly 1,400 euros. Over the past 20 years, switching costs have increased by roughly 50% in real terms, but in relation to average account balance, switching costs have not essentially changed. I conjecture that differences in the switching costs among the Finnish banks might be explained by differences in their loyalty programs.
URN:NBN:fi:bof-201909061438
Keywords: G21; L13; L49; 330